2014
DOI: 10.1016/j.jpsychires.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Association between binge eating disorder and changes in cognitive functioning following bariatric surgery

Abstract: Evidence suggests that both obesity and binge eating disorder (BED) may be associated with deficits in cognitive functioning. The purpose of this study was to examine whether a lifetime history of BED would be associated with changes in several domains of cognitive functioning (attention, executive function, language, and memory) following bariatric surgery. Participants were 68 bariatric surgery patients who completed a computerized battery of cognitive tests within 30 days prior to undergoing surgery and aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 49 publications
1
21
0
2
Order By: Relevance
“…In their longitudinal study, Alfonsson et al [14] also found a significant reduction on the Attention subscale of the ADHD Self-Report Scale [17] for men, but not for women. The finding of a better attention and memory function in the post-surgery sample is in line with the results of longitudinal studies demonstrating improvements in cognitive functioning following bariatric surgery [18,19,41,42]. It is reasonable to assume that postoperative cognitive improvement in attention and memory might have impacted the self-report on the respective CAARS subscale, possibly by way of improved prefrontal top-down control.…”
Section: Discussionsupporting
confidence: 84%
“…In their longitudinal study, Alfonsson et al [14] also found a significant reduction on the Attention subscale of the ADHD Self-Report Scale [17] for men, but not for women. The finding of a better attention and memory function in the post-surgery sample is in line with the results of longitudinal studies demonstrating improvements in cognitive functioning following bariatric surgery [18,19,41,42]. It is reasonable to assume that postoperative cognitive improvement in attention and memory might have impacted the self-report on the respective CAARS subscale, possibly by way of improved prefrontal top-down control.…”
Section: Discussionsupporting
confidence: 84%
“…Lavender et al . found that candidates with a lifetime history of BED were more likely to also have a history of depression, but after controlling for depression found no difference in attention, executive function or language functioning related to lifetime BED status. Friedman et al .…”
Section: Methodsmentioning
confidence: 91%
“…However, in contrast to expectations, BED and non-BED groups did not significantly differ in their respective degree of improvements over time. 108 In a recent study of patients with severe obesity, the surgery group (Roux-en-Y gastric bypass) “had higher remission rates and lower incidence rates of hypertension and dyslipidemia than did nonsurgery group 1 (P<0.05 for all comparisons).” 109 In addition, “among the patients in the surgery group who had type 2 diabetes at baseline, type 2 diabetes remitted in 66 of 88 patients (75%) at 2 years, in 54 of 87 patients (62%) at 6 years, and in 43 of 84 patients (51%) at 12 years.” 109 …”
Section: Management Of Obesity: Surgical Interventionsmentioning
confidence: 98%